2019
DOI: 10.18178/ijtef.2019.10.1.630
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Liquidity and Market Risk and the Effect on Bank Performance in Bahrain and Malaysia Banking

Abstract: This paper examines the determinants of liquidity and market risk of conventional and Islamic banks for two countries; Malaysia and Bahrain and the effect of the determinants on bank performance. Data were collected from 2008 to 2016 and analyzes using panel data analysis. The results reveal that bank capitalization and interest rate are significant determinants of liquidity and market risk respectively in both countries. In addition, banks capitalization and non-interest income/income attributable significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Some authors indicated that banks' sizes are extended through the new market entry or new branches development, incurring additional operating costs throughout the way and eroding their profits (Dietrich & Wanzenried, 2014). The size–profitability relationship has been, time and again, examined by prior works and evidence shows that size does have a role as a bank profitability determinant, with some of them supporting a positive bank size–bank performance relationship (Adelopo et al, 2018; Ali & Puah, 2019; Almaqtari et al, 2019; Bolarinwa et al, 2019; Menicucci & Paolucci, 2016; Pervan & Pelivan, 2015; Sahyouni et al, 2018; Zolkifli et al, 2019). Meanwhile, other empirical works showed a negative relationship between the two variables, and these include Batten and Vo (2019), Francis (2013), Menicucci and Paolucci (2016) and Supiyadi, Arief, and Nugraha (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors indicated that banks' sizes are extended through the new market entry or new branches development, incurring additional operating costs throughout the way and eroding their profits (Dietrich & Wanzenried, 2014). The size–profitability relationship has been, time and again, examined by prior works and evidence shows that size does have a role as a bank profitability determinant, with some of them supporting a positive bank size–bank performance relationship (Adelopo et al, 2018; Ali & Puah, 2019; Almaqtari et al, 2019; Bolarinwa et al, 2019; Menicucci & Paolucci, 2016; Pervan & Pelivan, 2015; Sahyouni et al, 2018; Zolkifli et al, 2019). Meanwhile, other empirical works showed a negative relationship between the two variables, and these include Batten and Vo (2019), Francis (2013), Menicucci and Paolucci (2016) and Supiyadi, Arief, and Nugraha (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, a robust capital structure is required by banks for economic development as it contributes to strengthening the financial crises and safeguards depositors in the face of instability in macroeconomic factors (Chowdhury & Rasid, 2015). In other words, capitalization is a must to ensure that the bank liquidity risk can be better managed (Zolkifli et al, 2019). Capitalization is referred to as an assessment tool for capital adequacy and for determining the bank's general soundness, representing its capitalization level.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations